Comparison of adjuvant emulsions for their safety and ability to enhance the antibody response in horses immunized with African snake venoms. (December 2022) - Arguedas, Mauricio; Umaña, Deibid; Moscoso, Edwin; García, Armando; Pereira, Carolina; Sánchez, Andrés; Durán, Gina; Cordero, Daniel; Sánchez, Adriana; Segura, Álvaro; Vargas, Mariángela; Herrera, María; et al.
Abstract: Adjuvant emulsions are widely used to enhance the antibody response in animals used as immunoglobulin source to produce snake antivenoms. We tested the performance of four commercial emulsion adjuvants (Montanide, Freund, Carbigen, and Emulsigen-D) and an experimental adjuvant (QH-769) in the antibody response of horses towards venoms of the African snakes Bitis arietans, Echis ocellatus, Dendroaspis polylepis and Naja nigricollis . Montanide, Freund and Carbigen adjuvants generated the highest immune response but induced moderate/severe local lesions at the site of injection. In contrast, Emulsigen-D and QH-769 adjuvants generated the lowest immune response and low incidence of local lesions. No evidence of systemic alterations was observed in the horses immunized with any of the adjuvants. It is suggested that the use of Montanide or Freund-based emulsions in the first immunization steps, followed by the use of Emulsigen-D, QH-769 or similar adjuvants in the following injections, could result in a satisfactory immune response against snake venoms, while not inducing serious local deleterious effects.